Comparison Of Post-Tonsillectomy Morbidity In Cases Of Sleep Apnoea Where Surgery Employed Either Cold Knife Or Coblation Techniques - Oghan, Fatih; Guvey, Ali; Aydemir, Onder; Erdogan, Onur; Fatih Topuz, Muhammet; Celiker, Metin; Terzi, Suat; Akbal, Seckin (ENT Updates, 2018)
Objective: To compare the snare and coblation methods in terms of post-tonsillectomy morbidity for patients with obstructive sleep apnoea. Method: The study involved 49 cases. Twenty-one patients were operated on using the snare method, whilst the remaining 28 patients underwent coblation tonsillectomy. The amount of intraoperative bleeding was recorded. The pain level at the 6th and 12th postoperative hour was assessed. On postoperative days 1, 3 and 7, the patients were assessed through VAS (Visual analogue scale) and Wong-Baker Faces Pain Rating Scale (WBFPRS). The two groups were then compared. The Tonsillar Fossa Wound Healing Score (TFWHS) assessment was also undertaken to assess wound healing rates on postoperative days 1, 3, 5, 7 and 10. Results: The patients who underwent coblation had significantly lower amounts of bleeding compared to those whose operations employed the snare method (p=0.046). Those patients who underwent tonsillectomy using the snare method had significantly higher 6th hour VAS and WBFPRS scores (p=0.011, p=0.005) than the other group. In contrast, VAS and WBFPRS scores at the 12th hour postop and on days 1, 2, 3 and 7 were similar between the groups. TFWHS for those who underwent coblation were significantly higher on days 1 and 3 (p=0.007; p=0.008). However these scores were similar on days 5, 7, and 10. Conclusion: The research indicates that the amount of intraoperative bleeding in cases undergoing coblation is significantly lower. Lower pain in the early postoperative period, resulting in earlier oral intake and better recovery scores for the tonsillary fossa seem to be the advantages of coblation as opposed to the snare method.